Spondias tuberosa (Anacardiaceae) leaves: profiling phenolic compounds by HPLC‐DAD and LC–MS/MS and in vivo anti‐inflammatory activity. (27th May 2016) - da Silva Siqueira, Emerson Michell; Félix‐Silva, Juliana; de Araújo, Lorena Maria Lima; Fernandes, Julia Morais; Cabral, Bárbara; Gomes, Jacyra Antunes dos Santos; de Araújo Roque, Alan; Tomaz, José Carlos; Lopes, Norberto Peporine; de Freitas Fernandes‐Pedrosa, Matheus; Giordani, Raquel Brandt; Zucolotto, Silvana Maria
Abstract: Spondias tuberosa is a medicinal plant used by several local communities in northeast Brazil to treat infections, digestive disorders and inflammatory conditions. The study aimed to identify and quantify the major phenolic in hydroethanolic extract of leaves from S. tuberosa and to evaluate its anti‐inflammatory potential. The chemical profile of extract was analyzed by HPLC‐DAD and HPLC–MS. The in vivo anti‐inflammatory activity was investigated in carrageenan‐induced hind paw edema and peritonitis models in mice. Identified and quantified through HPLC‐DAD or HPLC‐MS analyses of S. tuberosa extract were the following compounds: chlorogenic acid, caffeic acid, rutin and isoquercitrin. The inflammatory response to carrageenan was significantly reduced in both models by S. tuberosa extract. In hind paw edema, the edematogenic response was reduced by up to 63.6% and the myeloperoxidase activity was completely inhibited. In the peritonitis model, the total cell migration into the peritoneal cavity was reduced by up to 65%. The results obtained give evidence of the anti‐inflammatory action of S. tuberosa and suggest the potential therapeutic benefit of this plant on inflammatory conditions. The chlorogenic acid, caffeic acid, rutin and isoquercitrin identified and quantified in S. tuberosa leaves enable us to suggest that these compounds could be used as chemical markers for quality control of derivative products from this species. Copyright © 2016 John Wiley & Sons, Ltd.